IMF's role in structural adjustment - Collier, Paul (1999)
Argues that adjustment programmes have often been flawed by a lack of distributional analysis and by poor sequencing of reforms, notably premature financial liberalisation. Notes that as a result the programmes have caused avoidable hardship. Posits that conditionality has generally been ineffective in inducing policy reform, and that the attempt to taper out aid as part of the reform programme leads to avoidable reductions in post-stabilisation growth. Suggests that the Fund has an important role to play in post-stabilisation environments, through its potential to provide credible signals to private investors.